Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1985
DOI: 10.1002/1097-0142(19850315)55:6<1291::aid-cncr2820550623>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Further experience with regional radiofrequency hyperthermia and cytotoxic chemotherapy for unresectable hepatic neoplasia

Abstract: The authors report on 178 patients with unresectable hepatic tumors who have been treated with 1 to 25 (median, 6) courses of radiofrequency hyperthermia (RFHT) and chemotherapy. In 137 patients, the hepatic tumors consisted of metastases from colorectal adenocarcinomas. For patients who had no previous therapy and who had colorectal metastases with no extrahepatic disease, cumulative survival at 52 weeks' follow‐up was 80.5% and partial tumor regression was seen in 78.4%. Among the 69 patients who previously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Our inability to generate adequate liver hyperthermia is not unusual, as numerous other studies have documented difficulty in heating the liver with RF energy. A compilation of studies investigating the use of NiRFH on liver and liver tumors is shown in Table 1 [9][16], [29][31]. Most studies reported an inability to generate hyperthermia of greater than 40°C in 40% to 100% of patients in which thermometry was performed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our inability to generate adequate liver hyperthermia is not unusual, as numerous other studies have documented difficulty in heating the liver with RF energy. A compilation of studies investigating the use of NiRFH on liver and liver tumors is shown in Table 1 [9][16], [29][31]. Most studies reported an inability to generate hyperthermia of greater than 40°C in 40% to 100% of patients in which thermometry was performed.…”
Section: Discussionmentioning
confidence: 99%
“…Repeated exposures of this duration and frequency aims to mimic treatment schedules that would be anticipated for human use of a clinically adopted KNiRFH device, based off of previous reports of similar NiRFH devices [9][16]. For each treatment, general anesthesia was induced with intramuscular injection of telazol (4.4 mg/kg) and xylazine (2.2 mg/kg).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three so-called nonperturbing thermometry probes have recently become available. These are the Bowman thermistor [255], the Luxtron fluorescence fiberoptic probe [138,139,190], and the Christensen gallium arsenide fiberoptic probe [256]. However, tumour heating during thermotherapy is very uneven [257]; the information obtained from a single probe in a large, deeply situated cancer is not particularly meaningful.…”
Section: Noninvasive Regional or Local Hyperthermiamentioning
confidence: 99%
“…In 1983, the FRA was first introduced for hepatocellular carcinoma (HCC) treatment. [8] And then, the procedure has steadily become first-line ablative management of small to intermediate sized (ct cm) HCC at many centers. [9] RFA has a primary effectiveness rate of 88-99% in the management of HCC.…”
Section: Introductionmentioning
confidence: 99%